Online Learning Stress as A Moderator Between Learning Readiness, Learning Attitude, and Learning Students' Mental Psychological Performance: A Covid-19 Perception-Based View - Tang ShuPeng,; Jamalsafri Bin Saibon, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
After experiencing the COVID-19 pandemic, educational institutions have to shift their academic activities from manual to the online pattern. Online academic activities may cause attitudinal and behavioral changes in students' learning patterns. With the support of self-determination theory, the present study attempts to determine the role of the online learning climate in students’ performance. In addition, the current study also tries to determine the impact of the online learning climate on students' learning readiness and learning attitude. Moreover, this study also attempts to determine the mediating role of learning readiness and learning attitude in the relationship between online learning climate and students’ performance. To determine the moderating role of online learning stress in the relationship between learning reediness and student performance and between learning attitude and student performance is also an important objective of the current study. For empirical investigation, this study collected the data from 426 sports online learning students of different universities in China. The present study applied partial least square structural equation modeling for empirical analyses using Smart PLS software. The present study's findings acknowledge that online learning climate did not directly influence students’ performance; however, online learning climate has positive associations with learning readiness and learning attitude, respectively. Additionally, the present study’s outcomes confirm that learning readiness and learning attitude positively mediate the relationship between online learning climate and students’ performance, respectively. The present study's findings also revealed that online learning stress negatively moderates the relationship between learning readiness and student performance but does not moderate the relationship between learning attitude and student performance. The present study's findings also offer essential practical, theoretical, and managerial implications.